IMPLICANCIAS DE LA CAPACITACIÓN VIRTUAL EN LOS GOBIERNOS LOCALES - Bustamante Sánchez, Yolanda (2005)
Local governments in Peru have an important function in the decentralization process and the development of the country. However, there is a lack of real training programs for human resources in these institutions what make them unable to propose social projects. For this reason, it is necessary to promote long-distance (virtual) training courses on areas such as Public Management, Human Development, Citizenship Participation, Strategies for Managing Intergovernmental Policies, Public Administration.